Think again: Higher elasticity of substitution increases economic resilience - P. Dumas; S. Hallegatte (Fondazione Eni Enrico Mattei (FEEM), 2009)
This paper shows that, counter-intuitively, a higher elasticity of substitution in model production function can lead to reduced economic resilience and larger vulnerability to shocks in production factor prices. This result is due to the fact that assuming a higher elasticity of substitution requires a recalibration of the production function parameters to keep the model initial state unchanged. This result has consequences for economic analysis, e.g., on the economic vulnerability to climate change.
Keywords: D24; E17; E23; 330; Substitution; Calibration; Constant Elasticity of Substitution; Shock